Az örökbefogadás bírósági gyakorlata (1953–2014) - Rékasiné Adamkó, Adrienn (Díké - A Márkus Dezső Összehasonlító Jogtörténeti Kutatócsoport folyóirata, 2019)
The Act on Marriage, Family and Guardianship, which came into effect on January 1, 1953, was a milestone in the adoption legislation compared to the proposal of the Hungarian Private Law Code. It institutionalized the fate of orphans and half-orphans of world wars, and the specific purpose and desire of families without children, because by suppressing the former primary inheritance goal, it provided the child with proper education and care in the adoptive family. When the adoption contract was terminated, the legislator gave the guardianship authority the power of further authorizing adoption. The legal institution of secret adoption, which came into effect in 1974, created conditions for discreet adoption (incognito) so the adoptee’s “new” life and integration could be as harmonious as possible. In my study, I present the innovations of the Family Act, compared to the Proposal of the Private Law Code of Hungary, with the addition of judicial practice. My publication also reveals how the adopted child and the adoptive person were in a better position.